Recent Synthesis, Characterization, and Pharmacological Evaluation of Multifunctional Hemorphins Containing Non-Natural Amino Acids with Potential Biological Importance - Petar Todorov; Stela Georgieva; Jana Tchekalarova (MDPI AG, 2022)
The endogenous hemorphins are bioactive peptides with activity on opioid receptors. They are extensively studied and summarized in numerous reviews. During the last decade, several research teams have synthesized, characterized, and pharmacologically evaluated synthetic hemorphin analogs containing unusual amino acids, D-amino acids, α-aminophosphonic acids, and their derivatives. The present review summarizes the current studies on short-chain synthetic hemorphin peptide derivates containing non-natural amino acids. This review focuses on the structure-activity relationship analysis, details on specific methods for their characterization, and the advantage of synthetic hemorphin analogs compared to endogenous peptides as potent biologically active compounds with a complex mechanism of action.